Validity study of computer based Neo Personality İnventory’s Turkish version in terms of competency report - Koçyiğit, Seniha (My University, 2006)
Bu çalışmada Bilgisayar Destekli Türkçe NEO Kişilik Envanteri’nin ve envanterin yetkinlik raporunun geçerlilik analizi yapılmıştır. Bu amaçla Ernst & Young Danışmanlık şirketinin de izni ile şirketin databaseninde bulunan 3437 data rastgele seçilmiştir. (1853 bayan and 1584 bay, yaşları 13- 60 arasında) Çalışma iki aşamadan oluşmaktadır. Birinci aşamada, Onbeş farklı yetkinlik, yaş, cinsiyet, eğitim seviyesi ve eğitim alanı açısından analiz edilmiştir. İkinci aşamada, envanterin geçerlilik çalışması için faktör analiz yapılmış ve Faktör Analiz sonuçları temel alınarak envanterin 2 faktörlü bir yapısı olduğu tespit edilmiştir. Birinci faktör Dışadönüklük, ikinci faktör Deneyimlere Açıklık olarak isimlendirilmiştir. İlgili 2 faktör yaş, cinsiyet, eğitim seviyesi ve eğitim alanı açısından analiz edilmiştir. Çalışmanın istatistiksel sonuçları, kısıtlamalar, literatür ve ilerideki çalışmalar için öneriler ile birlikte tartışılmıştır.

The purpose of present study was to investigate the validity of Computer Based NEO Personality Inventory’s Turkish version and inventory’s’ competency report. For this purpose, by permit of Ernst & Young Company 3437 data ( 1853 female and 1584 male, age between 13 and 60) was randomly selected from the applicant database The study was conducted in two phases. In Phase I, 15 different competencies derived from the inventory was analyzed in terms of age, gender, educational background and level of education affect. In the second phase of the study factor structure of the NEO Personality Inventory’s Turkish version was examined using factor analysis. Results yielded two factors, the first factor was named Extraversion factor, and second factor was named Openness to Experience factors. These two new factors also analyzed in terms of age, gender, educational background and level of education affect. Literature correspondence is given & results are discussed along with the limitations of the study and suggestions for future research.
Keywords: Kişilik Envanteri; Yetkinlik